Feasibility Study in Implementation of Microgrid by using Fuel Cells - Ramani, Anis Niza; Gainus, Farlister Glenn; Sardi, Junainah; Mohd Nasir, Mohamad Na'im (2013)
Distributed generation or microgrid technology has the potential in reducing the stress faced by most power plants due to constant increase in electrical demand each year. This can help in reducing the need to construct new power plant which mostly requires large area and costly to be built. In this research, the feasibility of implementing fuel cells in microgrid is carried out. The fuel cell and the microgrid simulation model is modeled by using Matlab simulink. Both simulations are done in order to check the suitability of fuel cell stack output voltage which will be connected to the grid whereas this simulation is in ideal form. A 6-bus system network is modeled by using Matlab Power Simulation Analysis Tools (PSAT) in order to evaluate the potential of implementing microgrid in a bus system network. To evaluate the potential, three study cases have been done to this bus system network where a power generator with different power but same voltage is injected to the bus system for each study case respectively. The output of each study case in term of power loss and voltage drop is compared between the study case result and before the microgrid is injected to the bus system network. In the result obtained, the fuel cell stack output voltage after connected to the boost converter and three phase inverter shows convincing output voltage. The implementation of microgrid to bus system network also shows improvement in term of power loss and voltage drop. This means that fuel cells has the potential to be implemented in microgrid whereas microgrid is suitable to be implemented in a bus system network.